Gender Differences in the Effect of Depressive Symptoms on Prospective Alcohol Expectancies, Coping Motives, and Alcohol Outcomes in the First Year of College - Kenney, Shannon (J Youth Adolesc, 2015)
Problematic alcohol use and risk for dependence peak during late adolescence, particularly among first-year college students. Although students matriculating into college with depressive symptoms experience elevated risk for alcohol problems, few studies have examined the intervening mechanisms of risk. In this study, we examined depressed mood at college entry on prospective alcohol expectancies, drinking motives, and alcohol outcomes during the first year of college, adjusting for pre-college factors. Participants (N = 614; 59 % female, 33 % non-White) were incoming college students from three universities who completed online self-report surveys prior to matriculating into college and at the end of their first year in college. We utilized path analysis to test our hypotheses. In women, the path that linked depressive symptoms to consequences was primarily attributable to the effect of pre-college drinking to cope on drinking to cope in college, which in turn was associated with alcohol consequences. In men, the effect of depressive symptoms on alcohol consequences in college was independent of pre-college and college factors, thus indicating the need for research that identifies mechanisms of risk in males. Interventions that address coping deficits and motivations for drinking may be particularly beneficial for depressed adolescent females during this high-risk developmental period.